Definition of a High-Resolution Molecular Marker for Tracking the Genetic Diversity of the Harmful Algal Species Eucampia zodiacus Through Comparative Analysis of Mitochondrial Genomes - Zhang, Mengjia; Cui, Zongmei; Liu, Feng; Chen, Nansheng (Frontiers in Microbiology, 2021)
The cosmopolitan phytoplankton species Eucampia zodiacus is a common harmful algal bloom (HAB) species that have been found to cause HABs in essentially all coastal regions except the Polar regions. However, molecular information for this HAB species is limited with only a few molecular markers. In this project, we constructed the mitochondrial genome (mtDNA) of E. zodiacus, which was also the first mtDNA constructed for any species in the order Hemiaulales that includes 145 reported species (including two additional HAB species Cerataulina bicornis and Cerataulina pelagica). Comparative analysis of eight E. zodiacus strains revealed that they could not be distinguished using common molecular markers, suggesting that common molecular markers do not have adequate resolution for distinguishing E. zodiacus strains. However, these E. zodiacus strains could be distinguished using whole mtDNAs, suggesting the presence of different genotypes due to evolutionary divergence. Through comparative analysis of the mtDNAs of multiple E. zodiacus strains, we identified a new molecular marker ezmt1 that could adequately distinguish different E. zodiacus strains isolated in various coastal regions in China. This molecular marker ezmt1, which was ∼400 bp in size, could be applied to identify causative genotypes during E. zodiacus HABs through tracking the dynamic changes of genetic diversity of E. zodiacus in HABs.